Is There an Alternative to the Fiscal Compact for Conducting Fiscal Policy in the Euro Area? - Hallet, Andrew Hughes; Hougaard Jensen, Svend E. (Politik, 2013)
This paper o ers a critical assessment of the scal set-up in the Euro Area and considers a new framework for achieving scal discipline. e key idea is an inter-temporal assignment where national scal policies focus on long-term objectives and a common monetary policy on short-term objectives. e result is a self-stabilising set-up where the enforcement problem has largely been resolved. For practical implementation purposes, scal policy is stated in terms of a target for the public debt-to-GDP ratio. We argue that the debt target should be set in a forward-looking fashion to account for implicit liabilities, such as the discounted budgetary impact of changing demographics in addition to conventional debt measures.